Perencanaan Keuangan Bisnis Pengolahan Garam Industri Berkualitas dengan Berbasis Implementasi Teknologi - Gusnawati, Asma; Syah, Tantri Yanuar Rahmat; Negoro, Dimas Angga; Ruswanti, Endang (Prima Abdika: Jurnal Pengabdian Masyarakat, 2025)
The activity aims to analyze financial planning in a quality industrial salt processing business based on technology implementation. The research background is based on the still high national demand for industrial salt and the dominance of imports, so that a business strategy is needed that can produce quality salt through the use of modern technology. The PKM method is through initial preparation to identify partners and problems, conducting workshops, mentoring in technology implementation in the salt industry and monitoring and evaluating activity results. The implementation of technologies such as geomembranes, automatic pump systems, IoT-based sensors, and modern processing equipment requires relatively large capital investment, but can increase efficiency, quality consistency, and product competitiveness. Thorough financial planning includes estimating initial capital requirements, calculating operational costs, cash flow projections, break-even analysis, and evaluating investment feasibility through Net Present Value and Internal Rate of Return indicators. In addition, risk management aspects also play a crucial role in anticipating market price fluctuations, dependence on climate, technology maintenance costs, and industrial salt import policies.